2016
DOI: 10.2215/cjn.11961115
|View full text |Cite
|
Sign up to set email alerts
|

The See Kidney Disease Targeted Screening Program for CKD

Abstract: Background and objectives The effectiveness of targeted screening for identification of CKD is largely unknown. The See Kidney Disease (SeeKD) targeted screening project aimed to determine the prevalence of unrecognized CKD in Canada.Design, setting, participants, & measurements The SeeKD project was conducted across Canada using a convenience sample approach and events to identify adults with risk factors for CKD (i.e., diabetes, hypertension, vascular disease, family history of kidney problems, etc.). Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 24 publications
0
25
0
Order By: Relevance
“…96,97 The newfound opportunity with SGLT2 inhibitors highlights the urgent need for better CKD screening and detection. [11][12][13][14][97][98][99] Education and activation of patients regarding the benefits of receiving reninangiotensin system inhibitors and SGLT2 inhibitors can be accomplished through focused discussion and information dispersed in clinical settings, communities of highrisk groups, and public media platforms. For example, the NKF and CVS Kidney Care have partnered on a campaign to promote kidney health and screening for CKD.…”
Section: Benefits and Risks In Different Populationsmentioning
confidence: 99%
“…96,97 The newfound opportunity with SGLT2 inhibitors highlights the urgent need for better CKD screening and detection. [11][12][13][14][97][98][99] Education and activation of patients regarding the benefits of receiving reninangiotensin system inhibitors and SGLT2 inhibitors can be accomplished through focused discussion and information dispersed in clinical settings, communities of highrisk groups, and public media platforms. For example, the NKF and CVS Kidney Care have partnered on a campaign to promote kidney health and screening for CKD.…”
Section: Benefits and Risks In Different Populationsmentioning
confidence: 99%
“…Eligible participants were adults 18 years of age and older who provided informed consent. Details of the SeeKD programme and methodology have previously been reported [ 26 ]. In brief, all participants that attended a screening event were surveyed to gather baseline sociodemographic characteristics, risk factors for CKD, knowledge of kidney disease, current health behaviours, and to determine those at risk of CKD.…”
Section: Methodsmentioning
confidence: 99%
“…Gulla et al [32] pointed out the necessity of timely referrals of patients with CKD, and of a system to promote them, because referrals were often made too late. Galbraith et al [33] reported the results of the See Kidney Targeted Screening Program for CKD in Canada. A total of 6329 Canadians participated in the program, and 5194 with at least one risk factor were screened.…”
mentioning
confidence: 99%
“…(Also see, Komenda, Rigatto and Tangri [34].) Risk factors of CKD include obesity, hypertension, diabetes, kidney problems, high-risk ethic group, vascular disease, family history, preeclampisa, and smoking [33] [35] [36].…”
mentioning
confidence: 99%